Florida Dairy Industry Statistics: Economic Measures - Kathy G. Arriola; Albert De Vries (EDIS)
This 7-page fact sheet brings together key economic and price data about Florida’s primary dairy industry collected by the U.S. Department of Agriculture (USDA). Written by K.G. Arriola and A. De Vries, and published by the UF Department of Animal Sciences, February 2013.